2000
DOI: 10.1007/pl00013671
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of variable pitch cholesteric films and its relationship with the optical properties

Abstract: A way to make cholesteric films reflecting in a broad wavelength band consists in associating different cholesteric pitches in the same film. In two previous papers, we proposed an efficient method to produce variable pitch films, based on a thermal processing, and we studied the optical properties of these films with respect to the time of processing. In the present paper, we study the microstructure of such films with respect to the processing time by means of transmission electron microscopy. The cholesteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
53
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 10 publications
1
53
0
1
Order By: Relevance
“…1,2 Much attention has been recently focused on wide-band reflective polarizers (WBRPs) from cholesteric liquid crystals because they are of great importance for practical applications. [3][4][5] Introducing a pitch gradient is an ideal method for increasing the reflective bandwidth of a cholesteric liquid crystal. The pitch difference is often formed by the molecular diffusion of optically active monomers with different optical reactivities and fixed by photopolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Much attention has been recently focused on wide-band reflective polarizers (WBRPs) from cholesteric liquid crystals because they are of great importance for practical applications. [3][4][5] Introducing a pitch gradient is an ideal method for increasing the reflective bandwidth of a cholesteric liquid crystal. The pitch difference is often formed by the molecular diffusion of optically active monomers with different optical reactivities and fixed by photopolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…However, for some specific applications such as full-colour or white-or-black reflective displays, wide-band reflective polarisers are desired. Recently, much attention has focused on non-uniform pitch distribution in PSCLC to obtain a wide-band reflection effect (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The unsticking technique, having been used in fabricating dichroic sponge polymer dispersed liquid crystal (D-SPDLC) films (25), was introduced into the preparation of wide-band reflective cells in this study.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that introducing a pitch gradient (or forming a pitch difference) is an ideal method for increasing the reflection bandwidth of a Ch-LC [4,5]. Some widely investigated examples can be found in previous reports [4][5][6][7][8][9][10][11][12][13][14][15][16]. Recently, the choice of polymer stabilized cholesteric liquid crystals (PSCLCs) elaborated under specific ways has offered an important route to increase the reflection bandwidth [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%